Genetic investigations on causes of male infertility in Western Saudi Arabia. (24th March 2019) - Beg, Mohd A.; Nieschlag, Eberhard; Abdel‐Meguid, Taha A.; Alam, Qamre; Abdelsalam, Ahmed; Haque, Absarul; Mosli, Hisham A.; Bajouh, Osama S.; Abuzenadah, Adel M.; Al‐Qahtani, Mohammed
Abstract: In recent years, genetic studies have yielded great progress in elucidating causes of male infertility. This investigation aims to identify frequent genetic abnormalities, that is, sex chromosome aneuploidies and Y‐chromosome microdeletions among infertile men in Western Saudi Arabia. From a population of infertile patients, 88 male patients with either azoospermia or severe oligozoospermia (sperm concentration <5 million/ml) were selected. In addition to a thorough clinical workup, karyotypes and Y‐chromosomal microdeletions were investigated. Among those 88 infertile patients, we detected six patients with Klinefelter syndrome, two with 47 XYY syndrome and two with Y‐chromosome microdeletions AZFb, c. While the prevalence of sex chromosome aneuploidies was in the range of globally investigated populations, the microdeletions appeared to be less frequent in Western Saudi Arabia compared to other regions of the world. All genetically abnormal cases showed sperm concentration <1 million/ml, and hence, this appears to be the threshold for warranting genetic investigations in Western Saudi Arabia. Since Klinefelter and 47 XYY syndromes were only discovered late in life, upon an infertility investigation, sex chromosome aneuploidies due to their many‐fold comorbidities require earlier medical attention. A neonatal screening programme is suggested for detection of these aneuploidies in Saudi Arabia for the general health benefit of these patients.